Effects of geometry on large-scale tube-shear exfoliation of graphite to multilayer graphene and nanographite in water - Blomquist, Nicklas (Sci Rep, 2019)
Industrially scalable methods for the production of graphene and other nanographites are needed to achieve cost-efficient commercial products. At present, there are several available routes for the production of these materials but few allow large-scale manufacturing and environmentally friendly low-cost solvents are rarely used. We have previously demonstrated a scalable and low-cost industrial route to produce nanographites by tube-shearing in water suspensions. However, for a deeper understanding of the exfoliation mechanism, how and where the actual exfoliation occurs must be known. This study investigates the effect of shear zone geometry, straight and helical coil tubes, on this system based on both numerical simulation and experimental data. The results show that the helical coil tube achieves a more efficient exfoliation with smaller and thinner flakes than the straight version. Furthermore, only the local wall shear stress in the turbulent flow is sufficient for exfoliation since the laminar flow contribution is well below the needed range, indicating that exfoliation occurs at the tube walls. This explains the exfoliation mechanism of water-based tube-shear exfoliation, which is needed to achieve scaling to industrial levels of few-layer graphene with known and consequent quality.